Simulasi sederhana pada hukum pendinginan Newton - Iman Noor; Andry Fitrian (UNIVERSITAS INDRAPRASTA PGRI, 2021)
A simple simulations on Newton’s cooling law has been performed. This simulations aims to study correlation of the newton cooling constant at temperatures to cooling times. This reseach is displayed in GUI Matlab (Guide Using Interface). The input required is initial temperature, ambient temperature, cooling constant, and cooling time. Through numerical calculation of the Newton’s cooling equation with Eulerian Method, we got that the time to reach the ambient temperature of each cooling constant is 59 seconds, 31 seconds, and 20 seconds respectively.